Factors Related to The Incidence of Anemia in Young Girls at SMPN 4 Babelan, Bekasi - Nurevita, Ria; Widowati, Retno; Azzahroh, Putri (International Journal of Midwifery and Health Sciences, 2023)
Background: Anemia is a condition that often occurs in young women because they are still growing and entering puberty. Young women also experience menstruation every month which during this period they will be at risk of anemia. Other factors that can affect adolescent anemia are knowledge, diet, economic status, and consumption of iron supplement (Fe) tablets. Purpose: To determine the relationship between knowledge, menstrual patterns, economic status, diet, and adherence to consumption of Fe tablets with the incidence of anemia in young women at SMPN 4 Babelan, Bekasi Regency. Methods: This research uses descriptive analytic with cross sectional approach. The sample in the study amounted to 95 young women who had experienced menstruation with the non-probability sampling technique of taking samples in total sampling. The research instrument used a Hb check tool and a questionnaire. Results: The results of the study were tested by statistical tests using the chi-square test. Based on the results of statistical tests using chi square, it showed that factors related to the incidence of anemia were menstrual patterns (p=0.002), and factors that were not related to the incidence of anemia were knowledge (p=0.305), economic status (p=0.361), eating patterns (p=0.186), and consumption of Fe tablets (p=0.884). Conclusion: There was a significant relationship between menstrual patterns and the incidence of anemia in young women.